Autism Children Handling on Social Interaction - Asrizal, Asrizal (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This paper offers solutions for social workers in the treatment of autism in terms of social interaction problem. Social workers can practice it on the field in an attempt to deal with autism in social interaction through performing several approaches. Currently, many social workers do not know how to deal with autism who have problems in their social interactions, whereas the responsibility of social workers tasks are relegating autists in the community. This paper offers two forms of treatment of autism, early treatment and integratedhandling. This has become the focus of discussion in this paper to guide social workers no longer face trouble in handling social interaction of children with autism, which usually has been a problem in the fieldfor social workers.